2020
DOI: 10.46557/001c.17654
|View full text |Cite
|
Sign up to set email alerts
|

Did Bubble Activity Intensify During COVID-19?

Abstract: In this note, we utilize hourly exchange rate data for Japanese Yen, Canadian dollar, European Euro and the British pound to search for possible bubble type behavior. We identify evidence that bubble activity characterizes all four exchange rates more so in the COVID-19 period. We also show that bubble activity intensified during the COVID-19 period, implying markets became relatively more inefficient compared to the pre-COVID-19 period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(74 citation statements)
references
References 31 publications
(33 reference statements)
2
72
0
Order By: Relevance
“…P. K. Narayan (2020a) show that the Yen has become more resilient to shocks during the COVID-19 period. P. K. Narayan (2020b) shows that bubble activity in the Yen exchange rate has intensified in the COVID-19 period, rendering the market more inefficient. Moreover, Iyke (2020) shows that COVID-19 virus cases predict exchange rates.…”
Section: Introduction I Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…P. K. Narayan (2020a) show that the Yen has become more resilient to shocks during the COVID-19 period. P. K. Narayan (2020b) shows that bubble activity in the Yen exchange rate has intensified in the COVID-19 period, rendering the market more inefficient. Moreover, Iyke (2020) shows that COVID-19 virus cases predict exchange rates.…”
Section: Introduction I Introductionmentioning
confidence: 99%
“…In this paper, we examine whether the West Texas Intermediate (WTI) 1-month oil futures price predicts Japanese Yen. Our hypothesis is that the predictability relationship -that is, the ability of oil prices to predict exchange rates would have become stronger in the COVID-19 period because the Yen has become: (a) more resilient to shocks as demonstrated in the work of P. K. Narayan (2020a); and (b) has seen bubble activity intensify (P. K. Narayan, 2020b). For this reason, given the evolving literature on the Japanese market, in this study we focus on Japan.…”
mentioning
confidence: 99%
“…Several studies (see Devpura and Narayan, 2020;Haroon and Rizvi, 2020;Iyke, 2020a,b;Mishra et al, 2020;Narayan, 2020a;Narayan, Devpura, and Hua, 2020;Narayan, Phan, and Liu, 2020;Phan and Narayan, 2020;Prabheesh et al, 2020;Rath, and Akram, 2020;Salisu and and Akanni, 2020;Vidya and Prabheesh, 2020;Salisu and Sikiru, 2020; among others) argued that global markets and economies have been disrupted by the coronavirus pandemic. Recent studies have also shown that exchange rate market bubble activity has increased due to COVID-19 (Narayan, 2020b) and exchange rates have become more resilent due to the pandemic (Narayan, 2020c). We expect this disruption in global economic activities to have a significant impact on per capita income and TFP convergence across countries.…”
Section: Developed Developing Europementioning
confidence: 92%
“…First, this study is the first to examine the impact of COVID-19 on domestic credit to the private sector. Extant studies on the impact of COVID-19 on the financial sector have concentrated on the stock market returns and volatili-ties (Gil-alana & Claudio-Quiroga, 2020;Kp, 2020;Narayan et al, 2020;Salisu & Sikiru, 2020;Sharma, 2020), exchange rate (Narayan, 2020a(Narayan, , 2020b and insurance market development (Wang et al, 2020). This study complements the literature by examining the impact of the pandemic on domestic credit to the private sector by using the banking industry as a case study.…”
Section: Introduction I Introductionmentioning
confidence: 99%